ANALYSIS OF MAIN APPROACHES TO THE RISK DECREASING IN AGRI^ CULTURE - T. V. Dremova; A. N. Zharov; E. S. Titova (Овощи России, 2015)
Agriculture is one of the most risky sectors of any economy. Modern science and practice have developed various methods to reduce the riskiness of production, such as avoiding the risk, hedging, diversification and insurance. In this article we discuss ways to reduce these risks of production.